The reliability of the one maximum repetition in sedentary, active and strength-trained subjects Reprodutibilidade de uma repetição máxima em sujeitos sedentários, ativos e treinados em força - Carlos Leandro Tiggemann; Matheus Giacobbo Guedes; Roberta Bgeginsk; Ronei Silveira Pinto; Luiz Fernando Martins Kruel (Universidade Estadual Paulista (UNESP), 2011)
The aim of the study was to verify the reliability of one maximum repetition (1-RM) in three different groups, according levels of physical fitness. The sample was composed for thirty subjects (aged 18 to 34 years old) divided in three groups with ten subjects each: sedentary (SG), physical active (PAG) and strength-trained (STG). The subjects were submitted to two familiarization sessions and two sessions of maximum strength test (1-RM1 and 1-RM2) at the following exercises: bench press and 45º leg press. The comparison between 1-RM values was made by two-way ANOVA (test and group) and association between both by intraclass coefficient correlation (p ≤ 0.05). Data presented high correlation values between both tests (from 0.922 to 0.997; p < 0.001), however, significant differences (p < 0.05) was observed between 1-RM1 and 1-RM2 at bench press exercise in SG (56.40 ± 8.00 kg e 57.60 ± 7.89 kg, respectively), PAG (68,80 ± 9,26 kg e 69,40 ± 8,78 kg, respectively) and STG (87.20 ± 19.94 kg e 88.60 ± 19.86 kg, respectively), as well in the leg press in SG (222,5 ± 38,24 kg e 229,50 ± 38,55 kg, respectively), PAG (238.50 ± 26.25 kg e 244.00 ± 24.70, respectively) and STG (321.50 ± 46.19 kg e 336.40 ± 40.44 kg, respectively). It can be concluded that the subject's level of physical fitness does not appear to be a critical behavior at 1-RM reliability. O objetivo deste estudo foi verificar a reprodutibilidade do teste de 1-RM em três diferentes grupos, conforme seu histórico de prática de exercícios. A amostra foi composta por trinta sujeitos (entre 18 e 34 anos): sedentários (GSE, n = 10), fisicamente ativos (GFA, n = 10) e treinados em força (GTF, n = 10) e foram submetidos a duas sessões de familiarização e a duas sessões de testes de força máxima (1-RM1 e 1-RM2) nos exercícios supino reto e pressão de pernas 45°. Foi utilizado a ANOVA two-way (teste e grupo) e o teste de correlação intra-classe (p < 0,05). Verificaram-se altos valores de correlação entre os testes (de 0,922 a 0,997; p < 0,001), contudo, diferenças significativas (p < 0,05) foram encontradas entre 1-RM1 e 1-RM2 no exercício supino para o GSE (56,40 ± 8.00 kg e 57,60 ± 7,89 kg, respectivamente), GPA (68,80 ± 9,26 kg e 69,40 ± 8,78 kg, respectivamente) e GTF (87,20 ± 19,94 kg e 88,60 ± 19,86 kg, respectivamente), assim como no exercício pressão de pernas para o GSE (222,5 ± 38,24 kg e 229,50 ± 38,55 kg, respectivamente), GPA (238,50 ± 26,25 kg e 244,00 ± 24,70 kg, respectivamente) e GTF (321,50 ± 46,19 kg e 336,40 ± 40,44 kg, respectivamente). Logo, pode-se concluir que o perfil do histórico de prática de exercícios dos sujeitos parece não ser um fator decisivo no comportamento da reprodutibilidade dos testes de 1-RM.